1996
DOI: 10.1172/jci118901
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of the dermo-epidermal junction of skin regenerating from keratinocyte autografts. Anchoring fibrils are a target for tissue transglutaminase.

Abstract: Since transglutaminases create covalent ␥ -glutamyl-⑀ -lysine cross-links between extracellular matrix proteins they are prime candidates for stabilizing tissue during wound healing. Therefore, we studied the temporo-spatial expression of transglutaminase activity in skin regenerating from cultured epithelial autografts in severely burned children by the specific incorporation of monodansylcadaverine into cryostat sections from skin biopsies obtained between 5 d to 17 mo after grafting. The dansyl label was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 42 publications
(35 reference statements)
5
56
0
1
Order By: Relevance
“…Given the potential damage caused by hyperglycemia in both the glomerulus and mesangium (Mauer et al, 1984;Rasch, 1988;Ziyadeh and Goldfarb, 1991), the changes in ⑀-(␥-glutamyl)-lysine and tTg location would be consistent with the suggested role of tTg as a stress-related enzyme involved in tissue repair (Haroon et al, 1999;Mirza et al, 1997;Raghunath et al, 1996). However, previous studies have reported increased tTg levels accompanying externalization (Johnson et al, 1997 rather than just the redistribution of enzyme observed in the tubulointerstitium, an observation comparable to one we find in the glomerulus.…”
Section: Discussionmentioning
confidence: 74%
“…Given the potential damage caused by hyperglycemia in both the glomerulus and mesangium (Mauer et al, 1984;Rasch, 1988;Ziyadeh and Goldfarb, 1991), the changes in ⑀-(␥-glutamyl)-lysine and tTg location would be consistent with the suggested role of tTg as a stress-related enzyme involved in tissue repair (Haroon et al, 1999;Mirza et al, 1997;Raghunath et al, 1996). However, previous studies have reported increased tTg levels accompanying externalization (Johnson et al, 1997 rather than just the redistribution of enzyme observed in the tubulointerstitium, an observation comparable to one we find in the glomerulus.…”
Section: Discussionmentioning
confidence: 74%
“…No other family member had a skin disease or a genetic disorder. The affected members of family 3 included the 7-year-old proband (3-1), his 5-year-old brother (3-2), the 36-year-old mother (3-3), the 33-year-old aunt (3)(4), and the 65-year-old grandfather (3)(4)(5). The father and grandfather of 3-5 as well as 13 other relatives in five generations reportedly suffered from similar mechanically induced skin blistering.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to fibrin and fibronectin, tissue TGase has also been found to crosslink collagen III, V and VII [207], collagen XI, osteonectin [208] and osteopontin [8]. Localization of TGases has also been explored in ocular tissues [209][210][211].…”
Section: Tissue Transglutaminase Gluementioning
confidence: 99%